Megaloblastic anemia due to combined deficiency of Vitamin B12 and folic acid in an 8-month-old male child: A case report (Indian Journal of Case Reports, 2024)
A combined deficiency of vitamin B12 and folic acid is a rare condition that can cause megaloblastic anemia, pancytopenia, and neurological manifestations in infants. It can result from maternal dietary deficiency or malabsorption of these vitamins during pregnancy or lactation. We report the case of an 8-month-old male infant who presented with features of a combined deficiency of vitamin B12 and folic acid. His serum vitamin B12 and folate levels were low while serum ferritin, fibrinogen, triglycerides, lactate, ammonia, pyruvate, intrinsic factor antibody assay, and autoimmune workup were normal. He was treated with vitamin B12, oral iron, and folic acid supplementation and showed a prompt improvement in clinical picture and blood parameters within 7 days of therapy. This case highlights the importance of early diagnosis and treatment of a combined deficiency of vitamin B12 and folic acid in infants to prevent irreversible neurological damage and improve the outcome.